Prescribing Multiple Neurostimulants during Rehabilitation for Severe Brain Injury - Amy A. Herrold; Theresa Louise-Bender Pape; Ann Guernon; Trudy Mallinson; Eileen Collins; Neil Jordan (The Scientific World Journal)
Background. Despite a lack of clear evidence, multiple neurostimulants are commonly provided after severe brain injury (BI). The purpose of this study is to determine if the number of neurostimulants received during rehabilitation was associated with recovery of full consciousness or improved neurobehavioral function after severe BI. Method. Data from 115 participants were extracted from a neurobehavioral observational study database for this exploratory, retrospective analysis. Univariate optimal data analysis was conducted to determine if the number of neurostimulants influenced classification of four outcomes: recovery of full consciousness during rehabilitation, recovery of full consciousness within one year of injury, and meaningful neurobehavioral improvement during rehabilitation defined as either at least a 4.7 unit (minimal detectable change) or 2.58 unit (minimal clinically important difference) gain on the Disorders of Consciousness Scale-25 (DOCS-25). Results. Number of neurostimulants was not significantly (P>0.05) associated with recovery of full consciousness during rehabilitation, within one year of injury, or meaningful neurobehavioral improvement using the DOCS-25. Conclusions. Receiving multiple neurostimulants during rehabilitation may not influence recovery of full consciousness or meaningful neurobehavioral improvement. Given costs associated with additional medication, future research is needed to guide physicians about the merits of prescribing multiple neurostimulants during rehabilitation after severe BI.